High-energy electron emission from metallic nano-tips driven by intense single-cycle terahertz pulses - Sha Li (Nature Portfolio, 2016)
High-energy electron sources are powerful tools for investigating dynamics at atomic and subatomic scales. Here, Li and Jones demonstrate the terahertz-driven emission of electrons with energies exceeding five kiloelectronvolts from nano-tips and study its dependence on the tip radius.